ANALISIS PENDAPATAN USAHA TERNAK ITIK PETELUR DI KECAMATAN MOJOSARI KABUPATEN MOJOKERTO - Maydhy Zulfi Afied; Idah Zuhroh; Sri Budi Cantika Yuli (Jurnal Ilmu Ekonomi JIE, 2019)
This  research aims to : 1) profit of duck effort in Mojosari Regency, 2) efficiency and break even point of duck effort in Mojosari Regency and 3) factors were influenced of profit. This research uses descriptive  method with qualitatitve approach. The samples is 30 farmers determined by the sampling method by determining the criteria that have been determined from a population of 70 farmers. The data type used in this research are primary and secondary data. Methods of collecting data are observations and interviews. The results showed that the average income obtained by duck farmers in one production process (34 months) for 300-500 scale farmers was Rp 68,263,028, for 501-700 scale farmers was Rp 107,915,350, and 701-900 farmers was Rp 141,090,452. Livestock business has done efficiency because the R / C Ratio value is greater than 1 and the production results are able to exceed the results of the Break Event Point (BEP) calculation with details on a scale of 300-500 R / C ratio value 1.24, BEP (unit) 9,176 items, BEP (Rp) Rp. 14,666,784, while on the scale of livestock 501-700 R/C ratio 1.25, BEP (unit) 8,826 items, BEP (Rp) Rp. 14,185,732, and on the scale of livestock 701 -900 value of R / C ratio 1.26, BEP (units) 10,419 items, BEP (Rp) Rp 17,008,176. Simultaneously the cost of feed, the cost of vitamins and medicines, and total production have a very significant effect on income. Partially influential is the cost of feed and total production, while the cost of vitamins and medicine has no effect on income.